2005
DOI: 10.1080/00140130500101361
|View full text |Cite
|
Sign up to set email alerts
|

Arthro-kinematics of the elbow: study of the carrying angle

Abstract: The carrying angle of the elbow is usually assessed in full elbow extension, with a protractor goniometer, or derived from X-ray images. Substantial differences in carrying angle values have been reported, possibly explained by methodological differences. Carrying angles tend to show higher values in women than in men. The aim of this study was to confirm the previously described progressive decrease of the carrying angle as a function of increasing elbow flexion. After assessment of the carrying angle with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 9 publications
4
43
0
Order By: Relevance
“…23,24 This can be explained by differences in coordinate system definitions. As our focus was on kinematics, our reference (humerus) coordinate system was aligned with the flexion axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 This can be explained by differences in coordinate system definitions. As our focus was on kinematics, our reference (humerus) coordinate system was aligned with the flexion axis.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported this to be between 118 and 208. 23,[25][26][27][28] In order to compare our valgus angulation to a carrying angle measurement, the humeral deviation angle is added, which ranges from 18 to 148. 29,30 With this correction, we find that our valgus angulation of 68 corresponds to a range of 7-208, which is in agreement with the range of reported carrying angles.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is agreed that CA increases with age because of skeletal growth and development [1,16,24]. In regard to gender, CA is usually greater in females than males; however, this tendency cannot be generalised because of large inter-individual differences [22]. Some earlier studies reported a greater value of the CA on the dominant arm in both Turkish and Greek populations [16,21,24].…”
Section: Discussionmentioning
confidence: 94%
“…The CA plays an important role in load carrying, where it helps avoid contact with lower limb bones and allows positioning of the hand directly above the centre of mass of the carried weight, thus producing a comfortable lever arm [22]. Unilateral changes in the angle may indicate previous trauma, developmental anomaly, or may relate to repetitive stress in athletes [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…The labelling by the fuzzy classifier was verified by a human expert using Table 3 as a guide. The changes in the elbow angle and their indication of fatigue is based on a study by Van Roy et al (2005). This study claims that changes in the elbow angle of 1.8 +/-2.9 degrees in men indicates fatigue.…”
Section: Approaches In Labeling the Semgmentioning
confidence: 99%